The Study of Globalization from a Language Planning Perspective - Dekhir, Faiza; Abid, Samira (Richtmann Publishing, 2011)
This study is dedicated to describe Globalization from a language planning perspective. It also discusses how language planning can be used to provide a theoretical framework for Globalization. The nature of globalization will be examined in terms of, consequences, problems and solutions, among many other factors. In order for these objectives to be achieved, the researcher goes through the following definitions: Language planning definitions, globalization definitions, presentation of an accounting scheme for the study of language planning. This latter is meant to improve our ability to describe, predict and draw generalizations concerning Globalization.